Providing support to senior managers in schools via 'clinical' supervision: a purposeful, restorative professional and personal developmental space. Issue 1 (1st January 2019) - Reid, Hazel; Soan, Sue
Abstract: This paper reports on the first part of a research case study that provided senior leaders and SENCOs in schools with an opportunity to reflect on, air and discuss professional practice issues in a confidential, non-judgemental setting. The project was evaluated using qualitative questionnaires at three stages of the project and via a thematic analysis. The paper explains the genesis of the project and gives a brief overview of the relevant literature on clinical supervision. It outlines the model used and describes the process and issues identified. Key findings were that the participants found clinical supervision to be a powerful and restorative experience, professionally, personally and emotionally. National data detailing entry and retention figures to the teaching profession, alongside the pressures of meeting targets and work/life balance, suggest that the experiences of these seven participants in a small sample are not unusual or isolated. The findings will be of interest across the teaching profession.